Dampak Pandemi Covid-19 Terhadap Pendapatan Produsen Dealer Mitsubishi Di Jayapura - Christina Irwati Tanan; Alfredo Lelapary (Journal of Economics Development Issues, 2021)
The purpose of this study is to determine the efforts of Mitsubishi dealer manufacturers to increase revenue and efforts to overcome the obstacles faced during the Covid-19 Pandemic. The research was conducted at Mitsubishi Dealer PT. Bosowa Berlian Motor Jayapura and research data are income before and during the Covid-19 pandemic. The data analysis method is descriptive qualitative analysis. The results showed that the income of Mitsubishi Jayapura dealers during the Covid-19 Pandemic decreased when compared to before the Covid-19 Pandemic, which was an average of 51 percent. Efforts made by the Jayapura Mitsubishi Manufacturer Dealer, namely: Reduction of employees and many temporary laid-off employees, WFH, Sales Promotion via email and smartphone, implementing health protocols, reducing office operating hours, providing services through the Call Center. This research is an input for the Jayapura Mitsubishi Dealer Manufacturer to increase its income during the Covid-19 Pandemic. Keywwords: Producer;Income;The Covid-19 Pandemic Tujuan penelitian ini untuk mengetahui upaya produsen dealer Mitsubishi untuk meningkatkan pendapatan dan upaya untuk mengatasi kendala yang dihadapi pada masa Pandemi Covid-19. Penelitian dilakukan pada Dealer Mitsubishi PT Bosowa Berlian Motor Jayapura dan data penelitian adalah pendapatan sebelum dan pada masa pandemi Covid-19. Metode analisis data adalah analisis deskriptif kualitatif. Hasil penelitian menunjukkan Pendapatan Dealer Mitsubishi Jayapura pada masa Pandemi Covid-19, mengalami penurunan bila dibandingkan sebelum masa Pandemi Covid-19 yaitu rata-rata 51 persen. Upaya yang dilakukan Produsen Dealer Mitsubhisi Jayapura yaitu: Pengurangan Karyawan dan sejumlah karyawan dirumahkan sementara, WFH , Promosi Penjualan lewat email dan smartphone , menerapkan protokol kesehatan, pengurangan jam operasional kantor, pelayanan melalui Call Center . Penelitian ini sebagai masukan bagi Produsen Dealer Mitsubishi Jayapura untuk meningkatkan pendapatannya di masa Pandemi Covid-19 . Kata kunci:Produsen;Pendapatan;Pandemi Covid-19